Is advising food allergic patients to avoid food with precautionary allergen labelling out of date?. Issue 3 (June 2016) - Zurzolo, Giovanni A.; de Courten, Maximilian; Koplin, Jennifer; Mathai, Michael L.; Allen, Katrina J.
Abstract : Purpose of review: Precautionary allergen labelling (PAL) continues to be used by the food manufacturing industry to alert the food allergic consumer that cross-contact may have occurred during the supply chain for ingredients or the manufacturing process. This review will summarize recent evidence regarding use and interpretation of precautionary labels by industry, healthcare professionals, and food allergic consumers. Consumers find precautionary labels difficult to interpret and often distrust them as disclaimers of product liability. It is unclear from a clinician's perspective how healthcare professionals should advise their patients regarding these statements. Recent findings: Recent studies suggest that consumers do not always read food labels and that these labels are difficult to interpret and are often distrusted by consumers as disclaimers of liability. There is evidence to suggest that this behaviour occurs in all countries assessed that use PAL. The healthcare professional remains confused about the interpretation and value of the current PAL system as it is unclear whether foods that contain no advisory labels are safe to consume. There is a need for improvement in the value and use of precautionary labelling for allergen risk assessment for allergic consumers. Summary: New studies have shown the confusion that currently exists in regard to PAL for the healthcare professional and the consumer alike. The studies have also highlighted certain gaps in the literature that, once addressed, will improve the uniformity of PAL and provide the healthcare professional with appropriate advice which they can in turn relay to the allergic consumer. Because of the global supply of food products there is a need for an international approach in improving PAL.